Expectoration of tonsillar metastasis of pulmonary pleomorphic carcinoma after pseudoprogression: A case report. Issue 12 (11th May 2021) - Kuge, Tomoki; Okabe, Fukuko; Yamamoto, Yuji; Ishijima, Mikako; Uenami, Takeshi; Kanazu, Masaki; Akazawa, Yuki; Yano, Yukihiro; Yamaguchi, Toshihiko; Mori, Masahide
Abstract: Pulmonary pleomorphic carcinoma is a rare malignant tumor that grows rapidly and has a poor prognosis. Although no effective treatments have so far been established, immune checkpoint inhibitors (ICIs) have shown clinical improvement in some cases of pleomorphic carcinoma. However, pseudoprogression is a major concern for treatment of this carcinoma using ICIs. Here, we report the case of a 61‐year‐old man who was diagnosed with large cell carcinoma of the lung with brain metastases. Systemic chemotherapy comprising carboplatin and pemetrexed was administered as a first‐line therapy; however, disease progression was observed. A tonsillar lesion grew rapidly after the administration of nivolumab as a second‐line therapy. Tracheostomy was planned to avoid suffocation, but the patient naturally expectorated the tumor. Pathological examination revealed that it was a palatine tonsillar metastasis of pulmonary pleomorphic carcinoma with infiltration of CD8+/CD4‐ lymphocytes and necrosis. The primary lesion expanded after nivolumab administration and shrank with no additional nivolumab administration. We therefore concluded that pseudoprogression caused expectoration of the tonsillar metastasis. Hence, ICIs can cause serious adverse events due to pseudoprogression. Abstract : We report a case of expectoration of tonsillar metastasis of pulmonary pleomorphic carcinoma after administration of nivolumab. We concluded that pseudoprogression caused expectoration of tonsillar metastasis, since the specimen of biopsy from tonsillar metastasis showed infiltration of CD8+/4‐ cells. This rare condition assists in elucidating the mechanism of pseudoprogression.